2017
DOI: 10.1093/mnras/stx2947
|View full text |Cite
|
Sign up to set email alerts
|

RAiSE III: 3C radio AGN energetics and composition

Abstract: Kinetic jet power estimates based exclusively on observed monochromatic radio luminosities are highly uncertain due to confounding variables and a lack of knowledge about some aspects of the physics of active galactic nuclei (AGNs). We propose a new methodology to calculate the jet powers of the largest, most powerful radio sources based on combinations of their size, lobe luminosity and shape of their radio spectrum; this approach avoids the uncertainties encountered by previous relationships. The outputs of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(106 citation statements)
references
References 84 publications
(206 reference statements)
6
97
1
Order By: Relevance
“…On the other hand, it has recently been shown (Rodman et al 2019) that halo masses derived through optical galaxy clustering provides an excellent measure of jet environments. The RAiSE model has been shown to reproduce the observed relationship (Led-low & Owen 1996;Best 2009) between radio luminosity, morphology, and host galaxy properties (Turner & Shabala 2015); recover sub-equipartition lobe magnetic fields consistent with independent Inverse Compton measurements (Ineson et al 2017;Turner et al 2018b); and in combination with hydrodynamic simulations, reconcile the observed discrepancy between spectral and dynamical ages in powerful radio galaxies (Turner et al 2018a). RAiSE has subsequently been used to test jet production models (Turner & Shabala 2015), quantify the observability of low-power jets in poor environments (Shabala et al 2017), model remnant lobes (Turner 2018), and determine cosmological parameters from radio source observations (Turner & Shabala 2019).…”
Section: Radio Agn In Semi-analytic Environmentsmentioning
confidence: 55%
See 2 more Smart Citations
“…On the other hand, it has recently been shown (Rodman et al 2019) that halo masses derived through optical galaxy clustering provides an excellent measure of jet environments. The RAiSE model has been shown to reproduce the observed relationship (Led-low & Owen 1996;Best 2009) between radio luminosity, morphology, and host galaxy properties (Turner & Shabala 2015); recover sub-equipartition lobe magnetic fields consistent with independent Inverse Compton measurements (Ineson et al 2017;Turner et al 2018b); and in combination with hydrodynamic simulations, reconcile the observed discrepancy between spectral and dynamical ages in powerful radio galaxies (Turner et al 2018a). RAiSE has subsequently been used to test jet production models (Turner & Shabala 2015), quantify the observability of low-power jets in poor environments (Shabala et al 2017), model remnant lobes (Turner 2018), and determine cosmological parameters from radio source observations (Turner & Shabala 2019).…”
Section: Radio Agn In Semi-analytic Environmentsmentioning
confidence: 55%
“…First generations of radio source models used either constant (Begelman & Cioffi 1989) or simple power-law environments (Kaiser et al 1997;Heinz et al 1998) to describe such atmospheres; these models produced self-similar radio sources which are inconsistent with observations (Mullin et al 2008;Hardcastle & Krause 2013), and had limited use in interpretation of observations. More sophisticated treatment of radio source atmospheres naturally reproduces the observed narrowing of FR-II sources due to a rapidly declining atmosphere at large radii (Turner et al 2018b;Hardcastle 2018).…”
Section: Radio Agn In Semi-analytic Environmentsmentioning
confidence: 75%
See 1 more Smart Citation
“…The effect is caused by the motion of the masses, similar to the magnetic force being caused by the motion of electric charges. Massive black holes with sub-parsec separations can produce periods of the order of 10 6 years, significantly less than the typical ages of observed radio sources, 10 7 -10 8 years (e.g., Krause 2005;English, Hardcastle & Krause 2016;Harwood et al, 2017;Turner, Shabala & Krause 2018), such that jet-lobe asymmetries and jet curvature would be visible on radio maps of 100 kpc-scale jets.…”
Section: )mentioning
confidence: 93%
“…where s ≈ 2−2.5 is the power-law index of the electron energy distribution at the hotspot Willott et al 1999;Turner et al 2018b). Assuming typical β values between 0 and 2, the expected scalings are,…”
Section: Theoretical Considerationsmentioning
confidence: 99%